Design of the aerobic hail reactor - towards improved energy efficiency - Shaer, Gianluca Sasha Salvatore Ganter (Department of Chemical Engineering, 2023)
This dissertation presents the results of an investigation into the design of a novel low aspect ratio reactor, dubbed the HAIL (horizontal air-injected loop) reactor. Current industrial high cell density aerobic reactors for cultivation of bacteria and yeast are typically either stirred tank reactors (STR's), bubble column reactors (BCR's) or airlift reactors (ALR's). These systems can attain high mass transfer rates and short mixing times; however, their energy efficiency remains a concern. Many studies have attempted to further optimise these reactors, but they are ultimately limited by their high aspect ratios. These lead to large pressure heads that the air compressor needs to overcome on sparging, contributing significantly to energy costs. Low aspect ratio (LAR) reactors, such as the wave bag, orbital shaker and raceway reactors offer an alternative to these systems, providing superior energy efficiency for both mixing and aeration. However, each has core issues preventing their usage in high cell density aerobic culture. Their maximum mass transfer coefficient is typically too low to support high cell density cultures. Additionally, these reactors tend to have poor scalability, making them unfeasible for large scale industrial usage. To overcome these challenges, the HAIL reactor makes use of a tubular loop design. The anticipated benefit of the loop design was that it forces the air to travel the length of the reactor before leaving the system, enabling significant surface aeration and residence time in the reactor. These both impact the mass transfer coefficient. Additionally, the loops can be stacked upon one another, overcoming the scalability issue. The reactor would also be energy efficient based on its LAR. To establish target performance ranges, a literature review on the gas-liquid mass transfer coefficient, mixing time and efficiency of current low and high aspect ratio (HAR) reactors was conducted. This was supplemented with experimental results (including mass transfer coefficients, cell density and viscosity) from the fed-batch STR cultivation of Saccharomyces cerevisiae, an easy to work with highly aerobic yeast. A fed-batch feeding profile was developed for this. To better compare reactor performance, a term was introduced called the mass transfer energy efficiency, with units m3 ∙h -1 ∙W-1 , obtained via the quotient of the kLa and the power input per unit volume. The literature mass transfer energy efficiency ranges for the STR, BCR and ALR were found to be 0.022-0.236 m3 ∙h -1 ∙W-1 , 0.084-0.317 m3 ∙h -1 ∙W-1 and 0.142-0.493 m3 ∙h -1 ∙W-1 respectively, with maximum kLa values ranging up to 1000 h-1 depending on the power input. Mixing times for these systems differ depending on scale and configuration, ranging from below a minute up to 20 minutes. Experimental fed-batch and sterile water systems had efficiency ranges of 0.044-0.245 m3 ∙h -1 ∙W-1 and 0.059-0.285 m3 ∙h -1 ∙W-1 respectively, with a maximum kLa of 240 h-1 and 226 h-1 . Based on cellular growth results, the theoretical minimum kLa required was calculated as 372 h-1 . The most notable literature efficiencies for LAR reactors were held by the travelling loop, raceway, and wave reactors with ranges of 0.286- 0.295 m3 ∙h -1 ∙W-1 , 0.034-0.867 m3 ∙h -1 ∙W-1 , and 0.112-0.742 m3 ∙h -1 ∙W-1 . For the wave and travelling loop reactors, mixing times below a minute were attainable. A 6.2 L proof-of-concept and 31.4 L laboratory-scale prototype of the HAIL reactor were developed. In the proof-of-concept prototype, preliminary studies were carried out on the impact of sparger depth and angle on circulation time. Using the laboratory-scale system a range of sparger designs, including different angled jets, outlet areas and a circular sparger design, were investigated. The circular sparger design was found to be the ideal sparger type. A mixing time of 7-19 minutes depending on the power input was found for the 31.4 L configuration. The power efficiency range determined was 0.120- 0.281 m3 ∙h -1 ∙W-1 ; however, the calculation used to determine this is an underapproximation. The maximum kLa of 13.84 h-1 is an order of magnitude (between 10 and 100) lower than the values that can be obtained in HAR reactors for industrial aerobic culture. It was found that HAIL reactor performance did not change substantially with an increase in viscosity from 1 to 1.4 cP. The HAIL reactor did not compete with existing low and high aspect ratio reactors in its current configuration in terms of mass transfer. Additional research on the design is recommended to enhance gas - liquid contacting and associated mass transfer. These ongoing studies will enable the potential relevance and application of the novel reactor to be determined.